2021
DOI: 10.3390/molecules26227025
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Determinants for α1-Adrenergic/Serotonin Receptors Activity among Phenylpiperazine-Hydantoin Derivatives

Abstract: Several studies confirmed the reciprocal interactions between adrenergic and serotoninergic systems and the influence of these phenomena on the pathogenesis of anxiety. Hence, searching for chemical agents with a multifunctional pharmacodynamic profile may bring highly effective therapy for CNS disorders. This study presents a deep structural insight into the hydantoin-arylpiperazine group and their serotonin/α-adrenergic activity. The newly synthesized compounds were tested in the radioligand binding assay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The norbornene moiety of the ligands is directed towards the extracellular vestibule while the N -aryl group penetrates deeper into receptor aromatic microdomain which is in accordance with our previous results [ 22 , 23 ]. This is also in line with the data recently published by Kucwaj-Brysz et al [ 33 ], who identified molecular docking poses of serotonin receptor ligands with the arylpiperazine moiety deeply buried in the binding pocket. Moreover, such a ligand binding mode is in agreement with the one found for ritanserin in 5-HT 2C receptor (PDB ID: 6BQH [ 6 ]).…”
Section: Resultssupporting
confidence: 92%
“…The norbornene moiety of the ligands is directed towards the extracellular vestibule while the N -aryl group penetrates deeper into receptor aromatic microdomain which is in accordance with our previous results [ 22 , 23 ]. This is also in line with the data recently published by Kucwaj-Brysz et al [ 33 ], who identified molecular docking poses of serotonin receptor ligands with the arylpiperazine moiety deeply buried in the binding pocket. Moreover, such a ligand binding mode is in agreement with the one found for ritanserin in 5-HT 2C receptor (PDB ID: 6BQH [ 6 ]).…”
Section: Resultssupporting
confidence: 92%
“…The proper representation of MD outcome opens the door to the wide range of possibilities in terms of the post-processing approaches. Podlewska et al (2020) and Kucwaj-Brysz et al (2021) analyzed ligand-receptor contact patterns occurring during MD simulations and examined them with reference to the modeled property. Via the calculation of the Pearson’s correlation coefficient between the contact frequencies and values of examined parameters, the highest correlated residues (considered as the most important for the modeled property) were detected.…”
Section: Examples Of Ml-based Analysis Of MDmentioning
confidence: 99%
“…Moreover, ML can help in the compound optimization and indication of features, which are important for a particular type of activity, thanks to the wide range of interpretability tools ( Hudson, 2021 ). ML methods also support structure-based path of virtual screening tasks – they assist in the detection of ligand-protein interaction patterns characteristic for considered activity profiles ( Khamis et al, 2015 ; Khamis and Gomaa, 2015 ; Khamis et al, 2016 ), as well as in the detection of complex relationships between ligand-protein interaction schemes occurring during MD simulations ( Podlewska et al, 2020 ; Kucwaj-Brysz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%